Plug and play innosat ACS simulator - Siti Maryam, Sharun; Mohd Yusoff, Mashor; Fadzilah, Hashim (Penerbit UTM Press, 2015)
This research proposes a novel approach of satellite simulator design where the simulator will be in the form of both software and hardware. A software simulator will represent the satellite dynamics model, incorporating all the operating conditions of the satellite in orbit. The control algorithm for Attitude Control System (ACS) will be implemented on Rabbit Micro Controller (RCM4100) and the dynamics model of Innovative Satellite (InnoSAT) plant in PC have been tested using real-time hardware-in-loop-simulation (HILS) technique. The results that have been obtained show that the InnoSAT ACS simulator can produce as good result as MATLAB simulation for the InnoSAT plants. The MSE values that have been calculated also show that there are a close match between HILS and MATLAB simulation where the MSEs different value are small. From both results, it is enough to verify that the developed protocol working satisfyingly and seems to be possible to be implemented on the actual flight.